2016
DOI: 10.1080/14397595.2016.1177247
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Epstein–Barr virus load and killer T cells in patients with juvenile idiopathic arthritis treated with methotrexate or tocilizumab

Abstract: Treatment with MTX and/or TCZ did not severely affect EBV load and prevent induction of EBV-CTLs in JIA patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
1
6
1
Order By: Relevance
“…Our study showed significant (p = 0.021) decrease of EBV load under Tocilizumab, as published by others [ 23 , 24 ]. In a recent cross-sectional case-control study, Erre GL et al studied EBV load by Real time PCR in one hundred thirty-five Sardinians (77 RA patients and 58 healthy donors, HDs).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our study showed significant (p = 0.021) decrease of EBV load under Tocilizumab, as published by others [ 23 , 24 ]. In a recent cross-sectional case-control study, Erre GL et al studied EBV load by Real time PCR in one hundred thirty-five Sardinians (77 RA patients and 58 healthy donors, HDs).…”
Section: Discussionsupporting
confidence: 90%
“…Mourgues et al monitored EBV load in 20 patients with RA treated by tocilizumab and found no increase [ 23 ]. Fujieda et al followed Epstein-Barr virus load for three years in peripheral blood lymphocytes patients with juvenile idiopathic arthritis treated with methotrexate and tocilizumab and found it to decrease [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Published studies to date have not revealed differences in the number of EBV copies in the PBMC of patients with JIA compared to controls [9][10][11][12]. In our study, we did not observe any differences in the occurrence of EBV viremia in the studied groups, so the connection with the prevalence of arthritis was not demonstrated.…”
Section: Discussioncontrasting
confidence: 81%
“…Impairment due to EBV, as indicated by impaired T-cell response against EBV and increased EBV viral load after MTX administration, has been reported in patients with RA, 170 - 175 and several reports demonstrated the association between EBV viral road and disease activity in patients with juvenile idiopathic arthritis who developed MTX-LPD 176 . In contrast, several recent studies reported that the EBV viral load does not increase under the administration of ISDs such as MTX, TNFi, and ABT 177 - 179 …”
Section: Prediction Of Mtx-lpdmentioning
confidence: 99%